Comparison of analytical methods for detection of perchloroethylene glutathione conjugates and application in liver fractions - Coosen, Robin; Commandeur, J. (Student Undergraduate Research E-journal!, 2019)
Perchloroethylene (PER) is a degreasing solvent widely used to replace the toxic trichloroethylene. However, PER can also lead to nephrotoxicity via bioactivation by the glutathione (GSH) conjugative pathway. In this study, a postcolumn o-phtaldialdehyde (OPA)/N-acetylcysteine (NAC) derivatisation method has been developed and compared to existing methods for analysis of PER GSH conjugates. Subsequently, the rate of this conjugation has been studied for the first time in human subcellular fractions. The specific activity of PER GSH conjugation in humans shows significant interindividual differences and is 10-fold lower compared to rats, indicating that humans are less susceptible to nephrotoxicity via this pathway.